1989
DOI: 10.1103/physrevlett.62.3038
|View full text |Cite
|
Sign up to set email alerts
|

High resolution soft-x-ray tomography of sawtooth oscillations on the Tokamak de Varennes

Abstract: Up to five arrays of soft-x-ray detectors are used with the Fourier-Bessel harmonic reconstruction method to generate 2D images of sawtooth collapses during Ohmic plasma discharges on the Tokamak de Varennes. For low-harmonic reconstructions (M< 2), a quasi-interchange behavior (Wesson model) is observed during the sawtooth crash, but a reconnectionlike behavior (Kadomtsev model) is recovered using higher harmonics {M>L 3) on the same data. This indicates that the Kadomtsev model is a better description for th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
30
0

Year Published

1990
1990
2011
2011

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(33 citation statements)
references
References 15 publications
3
30
0
Order By: Relevance
“…It shows that, a large heat flow transfer across the x point of (both the m=1 and m=2) islands (C-E) and then the transferred energy gradually spreads poloidally over the peripheral region near the q=1 surface (E-F), while the reconstructed sawtooth crash process from total signals, as shown in the middle frames in Fig. 18, seems to be consistent with the Kadomtsev's model, which was also concluded in Ref [11]. The asymmetric heat flow can occur both in low field side and high field side, which is different from the observations in high β plasmas on TFTR [12].…”
Section: Experiments In Ht-7supporting
confidence: 83%
See 1 more Smart Citation
“…It shows that, a large heat flow transfer across the x point of (both the m=1 and m=2) islands (C-E) and then the transferred energy gradually spreads poloidally over the peripheral region near the q=1 surface (E-F), while the reconstructed sawtooth crash process from total signals, as shown in the middle frames in Fig. 18, seems to be consistent with the Kadomtsev's model, which was also concluded in Ref [11]. The asymmetric heat flow can occur both in low field side and high field side, which is different from the observations in high β plasmas on TFTR [12].…”
Section: Experiments In Ht-7supporting
confidence: 83%
“…Tomography of high-resolution soft-x-ray arrays can give the sawtooth crash structure. The Fourier-Bessel inversion method is used in the reconstruction by choosing M=2-3 and L=6-8 [11] . In order to present a clear picture of the crash, the sawtooth activity in Lower Hybrid Current Driven (LHCD) plasma is analyzed due to the large fluctuating amplitude (20-30% of the total emission in the central sightline) for distinguishing the crash and precursor stage.…”
Section: Experiments In Ht-7mentioning
confidence: 99%
“…So, the heat conduction and the particle convection along the field line, which are much greater than that across the flux surface, causes the very fast transfer of the heat and particles across the qϭ1 surface. This model is consistent with soft x-ray tomography, 2 but it is inconsistent with q profile measurements. 3 It has been suggested that a three-dimensional ͑3-D͒ reconnection 4 plays an important role in the sawtooth crash.…”
Section: Introductionmentioning
confidence: 51%
“…Here, m and n are the poloidal and the toroidal mode numbers, respectively. This model is consistent with the soft x-ray tomography measurement [4], but is not consistent with the observed crash time [5] or with the q profile measurement [6]. Considered three dimensionally, the full reconnection model implies that the set of reconnection points forms an m 1 helical line around the torus [7].…”
mentioning
confidence: 70%